ANALISIS KONSEPTUAL JENIS KURIKULUM BAHASA ARAB (GRAMATIKAL, FUNGSIONAL, NASIONAL, DAN MULTIDIMENSIONAL) - Fatimah, Salsabila Nova; Ridlo, Ubaid; Maswani, Maswani; Fakhrizal, Fakhrizal (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
This study aims to provide a conceptual analysis of four major Arabic language curriculum models-grammatical, functional, national, and multidimensional-within the context of Indonesian education. Employing a qualitative approach grounded in library research, the study uses content analysis to examine scholarly works, curriculum policy documents, and relevant prior studies. The findings indicate that the grammatical curriculum prioritizes mastery of linguistic structures as the foundation for understanding classical and textual traditions, while the functional curriculum highlights practical language use in everyday communicative situations. The national curriculum is characterized by its alignment with state educational standards, competency frameworks, and broader national objectives. Meanwhile, the multidimensional curriculum integrates linguistic, cultural, cognitive, and communicative components to address the demands of contemporary, 21st-century learning. The study concludes that a strategic integration of these four curriculum types is necessary to develop Arabic language instruction that is pedagogically relevant, communicatively effective, and capable of responding to ongoing processes of globalization, digitalization, and educational transformation in Indonesia.